Analysis of chromosome translocation frequency after a single CT scan in adults. (21st June 2016) - Abe, Yu; Miura, Tomisato; Yoshida, Mitsuaki A.; Ujiie, Risa; Kurosu, Yumiko; Kato, Nagisa; Katafuchi, Atsushi; Tsuyama, Naohiro; Kawamura, Fumihiko; Ohba, Takashi; Inamasu, Tomoko; Shishido, Fumio; et al.
Abstract: We recently reported an increase in dicentric chromosome (DIC) formation after a single computed tomography (CT) scan (5.78–60.27 mSv: mean 24.24 mSv) and we recommended analysis of 2000 metaphase cells stained with Giemsa and centromere-FISH for dicentric chromosome assay (DCA) in cases of low-dose radiation exposure. In the present study, we analyzed the frequency of chromosome translocations using stored Carnoy's-fixed lymphocyte specimens from the previous study; these specimens were from 12 patients who were subject to chromosome painting of Chromosomes 1, 2 and 4. Chromosomes 1, 2 and 4 were analyzed in ∼5000 cells, which is equivalent to the whole-genome analysis of almost 2000 cells. The frequency of chromosome translocation was higher than the number of DICs formed, both before and after CT scanning. The frequency of chromosome translocations tended to be higher, but not significantly higher, in patients with a treatment history compared with patients without such a history. However, in contrast to the results for DIC formation, the frequency of translocations detected before and after the CT scan did not differ significantly. Therefore, analysis of chromosome translocation may not be a suitable assay for detecting chromosome aberrations in cases of low-dose radiation exposure from a CT scan. A significant increase in the frequency of chromosome translocations was not likely to be detected due to the high baseline before the CT scan; the high and variable frequency of translocations was probably due to multiple confounding factors in adults.